Innovation Immigration Services in East Kalimantan (A Study in Samarinda and Balikpapan) - Indarto, Kus; Devianti, Risma Firdha; Patasik, Seloucus Gedzbal; Rahmadiansyah; Ratnawati, Susi (Journal of Transformative Governance and Social Justice, 2025)
Problems that often arise in passport processing are that the lack of firmness from officers results in people not queuing, delays in passport processing due to network damage, insufficient staff, cramped photo booths and frequent power outages, so that passport processing services are disrupted. This study aims to examine immigration service innovations at the Immigration Office in Samarinda and the Immigration Office in Balikpapan. To improve services to the community, agencies need to innovate their services. Innovation is essential for agencies to improve their services so that they can run efficiently and effectively. This research method used is descriptive qualitative. The data was collected through interviews, documentation and observatio Data analysis in this study combines two qualitative analysis methods, namely interactive analysis and network analysis. The research results show that there is an e-perdim innovation at the Class I TPI Immigration Office in Samarinda and an Amplang innovation at the Immigration Office in Balikpapan City. The e-perdim innovation at the Immigration Office in Samarinda has made it easier for the public to fill out perdim forms, allowing them to do so while seated more quickly and making the applicants’ handwriting easier to read. Meanwhile, the Amplang innovation at the Class I TPI Immigration Office in Balikpapan City has resulted in faster service and reduced parking congestion. Service Innovation Makes Service Delivery Easier, Faster, And Clearer Factors hindering innovation in immigration services in East Kalimantan Study at the Immigration Office in Samarinda and the Immigration Office in Balikpapan City. The barriers to innovation in e-perdim at the Immigration Office in Samarinda are occasional internet disruptions, elderly individuals who are unfamiliar with technology, and applicants’ mobile phones that are not compatible. Meanwhile, there are no barriers to innovation in Amplang at the Immigration Office in Balikpapan City. The factors hindering innovation are: The internet, which is a global communication network connecting all computers in the world regardless of their operating systems and hardware. The internet is necessary for easy access to important information